Multi-walled carbon nanotubes-ferroelectric liquid crystal nanocomposites: effect of cell thickness and dopant concentration on electro-optic and dielectric behaviour. Issue 11 (2nd September 2018) - Shukla, Ravi K.; Chaudhary, Ashok; Bubnov, Alexej; Raina, K. K.
ABSTRACT: Nanocomposites comprise functionalised multi-walled carbon nanotubes (0.00 wt%, 0.05 wt% and 0.07 wt%) and ferroelectric liquid crystals (FLCs) have been studied in the 5-μm- and 12-μm-thickness cells. Effect of anchoring energy and dopant concentration on the mesomorphic, electro-optic and dielectric behaviour of FLC has been explored. Fast switching time and increase in permittivity of non-doped FLCs and resulting nanocomposites as a function of increased cell thickness (from 5 to 12 μm) can be attributed to the change in the anchoring energy and direct current (DC) conductivity of the non-doped and doped systems. π–π stacking between carbon nanotubes and FLC layers give rise to the spontaneous polarisation of nanocomposites. Effect of cell thickness and anchoring energy on bistability are also discussed. Graphical Abstract: